The Significance of Pumpkin (Yaqṭīn) in Hadith and The Qur’an: A Bioactive Insight into Health and Healing - Faiz Hadi; Mazlan Ibrahim; Arif Yahya; Noraziah Mohamad Zin (Universiti Sains Islam Malaysia, 2026)
Journal of Hadith Studies, Volume 10 Issue 2 Page (71–90)